Implications of the Use of Eukaryotic Translation Initiation Factor 5A (eIF5A) for Prognosis and Treatment of Hepatocellular Carcinoma. (18th September 2012) - Shek, Felix H.; Fatima, Sarwat; Lee, Nikki P.
Abstract : Hepatocellular carcinoma (HCC) is a primary liver malignancy and accounts for most of the total liver cancer cases. Lack of treatment options and late diagnosis contribute to high mortality rate of HCC. In eukaryotes, translation of messenger RNA (mRNA) to protein is a key process in protein biosynthesis in which initiation of translation involves interaction of different eukaryotic translation initiation factors (eIFs), ribosome subunits and mRNAs. Eukaryotic translation initiation factor 5A (eIF5A) is one of the eIFs involved in translation initiation and eIF5A2, one of its isoforms, is upregulated in various cancers including HCC as a result of chromosomal instability, where it resides. In HCC, eIF5A2 expression is associated with adverse prognosis such as presence of tumor metastasis and venous infiltration. Based on eIF5A2 functional studies, suppressing eIF5A2 expression by short interfering RNA alleviates the tumorigenic properties of HCC cells in vitro while ectopic expression of eIF5A2 enhances the aggressiveness of HCC cells in vivo and in vitro by inducing epithelial-mesenchymal transition. In conclusion, eIF5A2 is a potential prognostic marker as well as a therapeutic target for HCC.